Soroprevalência do teste ML Flow em contatos de hanseníase de MinasGerais - Ana Regina Coelho de Andrade (2007)
Leprosy, an ancient and stigmatizing disease, is still a public health problem. The epidemiological control actions are based on the diagnosis and treatment of the leprosy patients and on household contacts surveillance. Although watching the contacts is a very important action in the control of this endemic disease, it doesnt occur satisfactorily. Serological tests in leprosy could help classify patients in paucibacillaryand multibacillary cases, as well as treat them properly. Moreover, they could identify among contacts which of them have subclinical infection and, therefore, a higher risk of developing leprosy in future. ML Flow is a serological test of quicker and easier execution which was applied in 2,840 household contacts of new cases of leprosy diagnosed from October 2002 to March 2004, in 13 municipalities of Minas Geraisstate, in a transversal and descriptive study. The variables considered were: gender, age, classification of index case, presence of BCG scar and detection rate in the municipalities where the research took place. ML Flow was positive in 20.5% of leprosy contacts. Seroposivity was higher among males (22.4%), people over 15 (21.7%), people in contact with multibacillary cases (23.9%), and people who lived in municipalities where the detection rate was very high (37.7%). The multivaried analysisshowed the chances of one household contact having seropositive test. This chance was related to household contact of multibacillary index case (OR=1.75), living in a municipality with a very high detection rate (OR=1,39), being over 15 (OR=1.38), and being a male contact (OR=1.25). The interpretation of these results support someepidemiological concepts already known in leprosy, such as a higher risk of getting leprosy among contacts of multibacillary cases and contacts living in an endemic area. The follow up of these contacts is, therefore, necessary and important to evaluate the real role of seropositivity in the development of leprosy disease among contacts.